Programmed Cell Death May Be Involved in the Seedless Phenotype Formation of Oil Palm - Htwe, Yin Min; Shi, Peng; Zhang, Dapeng; Li, Zhiying; Xiao, Yong; Yang, Yaodong; Lei, Xintao; Wang, Yong (Frontiers in Plant Science, 2022)
Oil palm (Elaeis guineensis Jacq.) is a well-known vegetable oil yielding crop. Seedless is one of the most prominent traits in oil palm due to its low processing costs and high oil content. Nevertheless, extensive study on molecular mechanisms regulating seedless formation in oil palm is very limited so far. In this study, we used stigma, style, and ovary from seedless and seeded (Tenera and Pisifera) oil palm trees to investigate the possible mechanism. Results showed that non-pollination resulted in no fruits, self- and cross-pollinations resulted in seedless fruits, while boron treatment had no effect on seedless formation, implying that seedless trees have incomplete self and outcrossing incompatibility. Furthermore, transcriptome data analysis showed eight programmed cell death (PCD) genes and three groups of PCD-related genes: 4-coumarate-CoA ligase (4CL), S-RNase and MADS-box. When compared to Tenera and Pisifera, the majority of these genes were significantly up-regulated in stigma and style of Seedless. In addition, co-expression network analysis confirmed the significant correlation among these genes. Moreover, two SSR markers (S41 and S44) were developed to identify the seedless phenotype. The up-regulation of 4CL and MADS-box TFs activated expression of PCD genes; on the other hand, S-RNase resulted in pollen tube RNA degradation and triggered PCD. While, the link between PCD and seedless phenotype formation in oil palm has rarely been studied in the past. Taken together, these findings provide new insight into the critical role of PCD in pollen tube lethality, resulting in double fertilization failure and the seedless phenotype.